The Effect of Corporate Image, Promotion, and Product Quality on Interest of TabunganKu Customers at PT Bank Mandiri Tbk - Afifah Al Mubarokah; Badri Markoni (Jurnal Aplikasi Manajemen dan Bisnis, 2022)
Banking in Indonesia is growing very rapidly, giving rise to intense competition between banks. One of the banks that survives in the midst of intense competition is PT Bank Mandiri. This study aims to determine and analyze the maker's image variable that influences the interest of TabunganKu customers. The object of this research is PT Bank Mandiri Tbk, Palembang A Rivai Area, which is a state-owned bank. This research uses quantitative methods, with purposive sampling technique. Primary data is obtained from data collection through questionnaires that have been filled out by the resource persons, and secondary data is obtained through journals, as well as the company's official website. The questionnaire wascalculated using the SPSS Ver application. 23 (Statistical Product and Service Solutions). The results in this study simultaneously maker image, promotion, and product quality have a positive effect on customer interest seen from the f value obtained, namely 13.450 with a significant value of 0.000. While partially only the image of the maker has a positive and significant effect on customer interest, for the promotion and product quality variables have no significant positive effect on customer interest. So that Bank Mandiri must strengthen and maintain the image of the company, as well as the image of its products, because that is the main attraction of Bank Mandiri, then improve promotion and product quality according to customer needs and the progress of the times.